Impact of Motor-Cognitive Interventions on Selected Gait and Balance Outcomes in Older Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Teraz, Kaja; Šlosar, Luka; Paravlić, Armin H.; de Bruin, Eling D.; Marusic, Uros (Frontiers in Psychology, 2022)
Background Efficient performance of most daily activities requires intact and simultaneous execution of motor and cognitive tasks. To mitigate age-related functional decline, various combinations of motor and cognitive training have shown promising results. The aim of this systematic review and meta-analysis of randomized controlled trials (RCTs) was to evaluate the efficacy of different types of motor-cognitive training interventions (e.g., sequential and simultaneous) on selected functional outcomes in healthy older adults. Methods Six online academic databases were used to retrieve eligible RCTs up to April 2021, following PRISMA guidelines and PICO criteria. A random-effects model was used for all meta-analyses conducted on selected functional outcomes: single- and dual-task gait speed, the Timed Up and Go Test (TUG), and Berg Balance Scale (BBS) score. Effect size (ES) was calculated as Hedges' g and interpreted as: trivial: <0.20, small: 0.20–0.60, moderate: 0.61–1.20, large: 1.21–2.00, very large: 2.01–4.00 or extremely large >4.00. Results From 2,546 retrieved records, 91 RCTs were included for meta-analysis (n = 3,745 participants; 64.7–86.9 years). The motor-cognitive interventions included differed according to the type of training (e.g., sequential, simultaneous with additional cognitive task or exergame training. The results showed that motor-cognitive interventions can improve gait speed under single-task conditions (small ES = 0.34, P = 0.003). The effect of the intervention was moderated by the type of control group (Q = 6.203, P = 0.013): passive (moderate ES = 0.941, P = 0.001) vs. active controls (trivial ES = 0.153, P = 0.180). No significant effect was found for dual-task walking outcomes (P = 0.063). Motor-cognitive intervention had a positive effect on TUG (small ES = 0.42, P < 0.001), where the effect of intervention was moderated by control group [passive (moderate ES = 0.73, P = 0.001) vs. active (small ES = 0.20, P = 0.020)], but not by the type of training (P = 0.064). Finally, BBS scores were positively affected by motor-cognitive interventions (small ES = 0.59, P < 0.001) with however no significant differences between type of control group (P = 0.529) or intervention modality (P = 0.585). Conclusions This study provides evidence for the effectiveness of various types of motor-cognitive interventions on performance-based measures of functional mobility in healthy older adults. With respect to significant effects, gait speed under single-task condition was improved by motor-cognitive interventions, but the evidence shows that this type of intervention is not necessarily more beneficial than motor training alone. On the other hand, motor-cognitive interventions are better at improving multicomponent tasks of dynamic balance and mobility function, as measured by the TUG. Because of substantial heterogeneity and the current limited availability of different types of interventions, the conclusions should be interpreted with caution.